A improved F‐expansion method and its application to Kudryashov–Sinelshchikov equation. (10th July 2013) - He, Yinghui; Li, Shaolin; Long, Yao
<x xml:space="preserve">Abstract</x> On the basis of the F‐expansion method with a new sub‐equation and Exp‐function method, an improved F‐expansion method is introduced. As illustrative examples, the exact solutions expressed by exponential function, hyperbolic function of Kudryashov–Sinelshchikov equation for arbitrary α, β are derived. Some previous results are extended. The method is straightforward, concise and is a promising and powerful method for other nonlinear evolution equations in mathematical physics. Copyright © 2013 John Wiley & Sons, Ltd.